Analysis and optimization of induction heating processes by focusing the inner magnetism of the coil. (1st September 2022) - Cui, Peng; Zhu, Wenbo; Ji, Hongjun; Chen, Hongtao; Hang, Chunjin; Li, Mingyu
Highlights: A super-heating efficiency strategy for optimization of induction heating processes by focusing inner magnetic of coil is proposed. Nearly 6.5-fold of the energy was saved by the focused induction heating method of the FIHM, comparing the traditional induction heating method. A detailed effect mechanism for six structural parameters of FIHM on temperature and magnetic field is studied. An experiment is carried out to verify the accuracy of optimization analysis and engineering feasibility. Abstract: Induction heating has been widely applied in the energy and manufacturing industry for its energy-saving, low-cost, local high-efficiency heating, and noncontact benefits. However, the energy efficiency of the induced magnetic field is normally limited for the magnetic scattering effect. To improve the energy and hence heating efficiency, a focused induction heating method (FIHM) has been proposed in this work by using the conical ferrite to focus inner magnetic of the coil. Meanwhile, a numerical model has been established to predict the electromagnetic and thermal distribution during the FIHM process. Traditional induction heating head and two focused induction heating heads (solid ferrite head and drilled-ferrite head) are compared to reveal the influence mechanism of different induction heating heads on the soldering of the pin-through-hole. The results show that the FIHM with drilled-ferrite head can improve the heating efficiency significantly by approximately 6.5-fold when compared to traditional induction heating, leading to a corresponding outstanding temperature increase over 296 °C within 1.5 s. Furthermore, the detailed effect mechanism for the six structural parameters of the FIHM on the temperature and magnetic field is studied. This study finds that the distance from the ferrite to the tin ring has the most significant effect, causing a temperature difference of about 560 °C. Finally, all these findings have been validated by the soldering experiments, and robust interconnection of deep pin-through-hole joints has been achieved through FIHM without voids. The work provides a theoretical basis and practical guidance for induction heating techniques with excellent electromagnetics and engineering application potential.